2008
DOI: 10.1159/000109386
|View full text |Cite
|
Sign up to set email alerts
|

Intragastric Balloon: Ethics, Medical Need and Cosmetics

Abstract: The development of the intragastic balloon as a safe, noninvasive, alternative method to weight reduction raises all the ethical questions routinely faced by practitioners of other forms of cosmetic surgery. In the case of the morbidly, severely or merely obese, the surgeon is faced with a medical decision in a situation defined by medical parameters. The case of the overweight or normal may, however, create an ethical dilemma in which the doctor is forced to make decisions of a nonmedical nature, for which hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…IGB models approved for use in most countries include “traditional” fluid filled (6 mo and one year), adjustable fluid filled (one year), and air filled (6 mo). The mechanism of action of IGBs is not yet fully established; however, it is believed that it is related to three factors: (1) Mechanical restriction, decreasing gastric capacity and leading to an increase in gastric emptying time, resulting in early satiety; (2) Hormonal changes due to direct contact with the gastric fundus, leading to a decrease in ghrelin and an increase in cholecystokinin, altering appetite and gastric emptying; and (3) Neurogenic, via central stimulation of the paraventricular nucleus of the solitary tract through vagal stimulation[ 8 ].…”
Section: Resultsmentioning
confidence: 99%
“…IGB models approved for use in most countries include “traditional” fluid filled (6 mo and one year), adjustable fluid filled (one year), and air filled (6 mo). The mechanism of action of IGBs is not yet fully established; however, it is believed that it is related to three factors: (1) Mechanical restriction, decreasing gastric capacity and leading to an increase in gastric emptying time, resulting in early satiety; (2) Hormonal changes due to direct contact with the gastric fundus, leading to a decrease in ghrelin and an increase in cholecystokinin, altering appetite and gastric emptying; and (3) Neurogenic, via central stimulation of the paraventricular nucleus of the solitary tract through vagal stimulation[ 8 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, IGB insertion represents a generally safe, easy to perform, adjustable, reversible, and reproducible endoscopic gastric restriction procedure, successfully applied for weight loss over the last 30 years. It covers a broad spectrum of indications from the overweight to the obese individual who does not fulfill the criteria for bariatric surgery, up to the morbidly obese, who qualifies for bariatric surgery but has uncontrolled co-morbidities causing her/him to be of high-risk for anesthesia and surgery or denied anesthesia and/or surgery, or its use as a bridge to bariatric surgery, and, finally, to anyone who just needs to achieve limited weight reduction, either prior to surgery of whatever kind and for whatever reason or merely for aesthetic purposes[ 51 , 82 , 83 ]. Generally speaking, the specific indications for balloon implantation for each candidate for such treatment must be built on the absolute judgment of the treating physician or the multidisciplinary working team; however, the positive response, that is the weight loss, is due exclusively to the responsibility of the patient to strictly adhere to a diet/exercise program and follow-up sessions throughout the treatment period, whatever type of balloon has been used.…”
Section: Discussionmentioning
confidence: 99%
“…The IGB has been also used as preparation for major surgical procedures to minimize anesthesia risk [6], and it has been indicated that it can be safely applied in morbidly obese patients before bariatric procedures to decrease morbidity and mortality following definitive surgery [12,13]. Left hepatic lobe volume decrease facilitates the laparoscopic procedures [3].…”
Section: Discussionmentioning
confidence: 99%
“…The method had to be abandoned in the late 1980s in the USA because of complications, but research continued in Europe resulting in a better understanding of its effects and the definition of suitable patients [2]. The potential benefit of IGB treatment is a sustained 5-10% weight loss in order to prevent obesity, and related co-morbidities and diseases [3]. Many years of research and design modifications have resulted in a growing interest from surgeons in recent years and increased use of IGB treatment [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation